ISLAMIC RELIGIOUS EDUCATION LEARNING BASED ON MULTILITERACY TO IMPROVE MODERATE ISLAMIC UNDERSTANDING - Qoidul Khoir; Rusik (As-Sulthan Journal of Education, 2025)
This research examines the role of multiliteracy in Islamic Religious Education (PAI) learning to strengthen moderate Islamic understanding among students. The background of this research is based on the importance of presenting learning strategies that can integrate text, digital, visual, cultural, and information literacy in facing the challenges of the globalization era. The research aims to describe the application of multiliteracy in Islamic Religious Education (PAI) and analyze its correlation with strengthening moderate Islamic values. This research uses a qualitative approach with a case study design, employing in-depth interviews, observation, and documentation with teachers and students in the madrasah environment. The research findings indicate that text literacy (82%) and cultural literacy (80%) are dominant aspects in supporting moderate attitudes, while digital literacy (75%) and visual literacy (68%) also enrich students' perspectives in understanding contemporary religious issues. The correlation between multiliteracy and moderate Islamic understanding reached an average of 78%, indicating a significant influence. In conclusion, multiliteracy in Islamic Religious Education (PAI) not only broadens students' horizons but also serves as a transformative strategy that bridges religious texts with modern social realities, making it relevant in shaping a tolerant, inclusive, and adaptive generation of Muslims. Keywords: multiliteracy, Islamic religious education, moderate Islam